The Relationship between Nurses' Knowledge about Emergencies and Code Blue Activation Decisions - Hikmah Lia Basuni; Yayan Gusman; Maruli Taufandas; Apriani Susmita Sari (Babali Health, 2024)
Introduction: Emergency conditions can occur anytime and anywhere, inside and outside the hospital. In-hospital cardiac Arrest (IHCA) is an emergency case that requires immediate treatment with varying survival rates in each hospital. Cardiac arrest in a hospital environment can occur in outpatients, patient families, visitors, hospital personnel and patients who are undergoing treatment. The initial principle of handling cardiac arrest is how nurses can recognize early signs of an emergency and decide to activate code blue as a sign that an emergency case has occurred and requires the assistance of a unique team from the hospital. Objective: This study aims to determine the relationship between nurses' knowledge of emergencies and the decision to activate Code Blue. Methods: This research is a quantitative research with an analytical survey method using cross-sectional research. In this study, the non-parametric Spearman rank correlation test was carried out at the. Sampling used total sampling technique and obtained 70 respondents. Results: There is a relationship between nurses' knowledge about emergencies and the decision to activate code blue at with a significant value of p= 0,000 (p < α 0.05), r = 0.601. Conclusion: There is a relationship between nurses' knowledge about emergencies and the decision to activate code blue. Training resuscitation skills and increasing nurses' knowledge through regular training, workshops, or code blue simulations are recommended, especially for patient care units that rarely activate code blue.